2010
DOI: 10.1016/j.brainresbull.2010.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus accumbens lesions modulate the effects of methylphenidate

Abstract: The psychostimulant methylphenidate (MPD, Ritalin) is the prescribed drug of choice for treatment of ADHD. In recent years, the diagnosis rate of ADHD has increased dramatically, as have the number of MPD prescriptions. Repeated exposure to psychostimulants produces behavioral sensitization in rats, an experimental indicator of a drug’s potential liability. In studies on cocaine and amphetamine, this effect has been reported to involve the nucleus accumbens (NAc), one of the nuclei belonging to the motive circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 76 publications
(132 reference statements)
1
38
0
Order By: Relevance
“…The NAc has historically been considered a key center in the behavior response elicited by psychostimulants such as MPD (Kim et al 2009;Pierce and Kalivas 1997b;Podet et al 2010). For example, it has been demonstrated that MPD can act as a rewarding and reinforcing stimulus in inducing self-administrative behavior and conditioned place preference (Bergman et al 1989;Kollins et al 2001;Martin-Iverson et al 1985;Meririnne et al 2001;Mithani et al 1986).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The NAc has historically been considered a key center in the behavior response elicited by psychostimulants such as MPD (Kim et al 2009;Pierce and Kalivas 1997b;Podet et al 2010). For example, it has been demonstrated that MPD can act as a rewarding and reinforcing stimulus in inducing self-administrative behavior and conditioned place preference (Bergman et al 1989;Kollins et al 2001;Martin-Iverson et al 1985;Meririnne et al 2001;Mithani et al 1986).…”
Section: Discussionmentioning
confidence: 99%
“…HA represents overall locomotor activity as recorded by beam breaks from one beam to the next. NOS, on the other hand, counts the number of small, repetitive movement episodes during which an animal breaks the same beam repeatedly, with at least 1 s between each episode Eckermann et al 2001;Gaytan et al 2000aGaytan et al , 2000bPodet et al 2010). Thus, in general, as an animal increases (or decreases) its movements after drug administration, it also increases (or decreases) the number of beam breaks it performs.…”
Section: Behavioral Apparatusmentioning
confidence: 99%
See 3 more Smart Citations